Development and psychometric validation of a multidimensional scale on the self-care needs of dependent people - Dixe, Maria dos Anjos (2022)
Objectives: To develop and validate an interprofessional, multidimensional self-care needs scale of dependent people. Methodology: After a literature search, 61 items were identified and divided into nine self-care dimensions. The items were then reviewed by an expert panel (N = 11) to confirm the content validity of the scale. Refined items were pilot-tested in 12 patients, using a 5-point Likert-type scale. A final version was generated and psychometrically tested in 143 dependent men and women aged 37–102 (80.7 ± 10.1) years. Results: The nine multidimensional self-care needs scales were developed on a broad theoretical and empirical basis. The scales showed very good psychometric properties, having adequate characteristics, satisfactory reliability, and good validity. Conclusions: The scales have good psychometric properties, with minor differential item functioning. The scales can be used by health professional and policy makers to measure dependent people’s self-care needs. Nevertheless, it is necessary to perform further psychometric validations using a larger sample. This is an appropriate tool for application in clinical and research settings to assess patients’ self-care needs.